Analisis Pengaruh Aktivitas Pasar Tradisional Marisa Terhadap Kinerja Ruas Jalan Sultan Amai Kecamatan Marisa Kabupaten Pohuwato - Rudi, Rudi; Urfan, Urfan; Dharmawan, Marcel Hendri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The aim of this research is to determine the influence of Marisa Traditional Market activities on the performance of Marisa District Roads, Pohuwato Regency. The research was carried out at the Marisa Traditional Market, Jalan Sultan Amai, Marisa District, Pohuwato Regency using data analysis, namely vehicle volume (Q), free flow speed (Fv), capacity (C), degree of saturation (DS) and service level. The research results show that the vehicle volume at the morning peak hour is 373.53 vehicles/hour. The vehicle volume during the afternoon peak is 363.27 vehicles/hour and in the afternoon it is 450.10 vehicles/hour. Traffic speed (Fv) is 37.04 km/hour. The capacity value (C) is 2,249.84 pcu/hour. The degree of saturation (DS) value was 0.16 for the first day of observation, 0.17 for the second day of observation and 0.20 for the third day of observation. From the degree of saturation value, the level of service (LoS) value is obtained, namely A. Based on the characteristics of the level of service, this means free flow, low volume and high speed. The driver can choose the desired speed.